Characteristics of a round-off movement and its changes resulting from connection to a stretched backward somersault - Asano, Y.; Okabe, F.; Fujita, Z.; Tsuchiya, J. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
The purpose of this study was to clarify the characteristics of twisting motion during a round-off, and its changes resulting from connection to a stretched backward somersault in gymnastics floor exercise. Eight male gymnasts performed a round-off (i.e., round-off trial) and a round-off to a backward stretched somersault (i.e., round-off somersault trial). Each of the trials was videotaped with 4 cameras operating at 120 fps to obtain 3-dimensional coordinate data. The time for a round-off, the center of mass of the hands and feet, the velocity of the center of body mass, the rotation angle about the longitudinal axis of the body (i.e., twist angle of round-off), the torsion angle of the torso, the shoulder joint angle, and the hip joint angle were calculated. The results indicated that the twist angle of round-off increased continually, starting before hand contact with the floor and ending when the hands left the floor. The round-off twist was not only generated by hip abduction at the stepping leg, but also promoted by the upward swing motion of both legs through his back side. The round-off trial temporarily formed a deeply flexed lunging position to increase the velocity of the center of body mass in the frontal direction. Also, the backward upswing of the legs rotated the lower torso, thus restraining the torso torsion. To gain the required rotational magnitude for a somersault, gymnasts flexed the hip in the air so that the feet came closer to the hand.